How a little design project means a lot to a community: Lessons learnt from the power of partnerships in the design of Anganwadi in Ajjarkad, Karnataka, India - Ang, Susan; Mohd Nawawi, Norwina; Nandineni, Ramadevi (2019)
Social responsibility is an ethical ideology or theory that an entity, be it an organization or individual has an obligation to act to benefit society at large (ARCASIA 2012). Building a better world is a global imperative to achieve the vision and aspirations of the United Nations Charter, to be “architects of a better world” through effecting positive social change, cultural preservation and issues of inequalities related to access to basic needs, women’s empowerment and children’s education. Social responsibility in architecture is about designing spaces and environments that are accountable and accessible to the interests of stakeholders; engender trust, respect and ownership in accordance to the Rule of Law and Respect for Human Rights. In designing social responsibility architecture and built environment, it is argued that these concerns can only be successfully achieved through platforms of global intercultural education, with collaboration and partnership as well as stewardship of the local government including community resources. This paper explored Intercultural Dialogue through Design (iDiDe), immersive learning, community stakeholder engagement and consultation methods in the design of an Anganwadi building in Ajjarkad, Karnataka, India as the case study. iDiDE, as architecture and built environment education platform, explores student learn-ing experiences and measure qualitatively the value of the design outcomes that benefit the community. This paper reflects upon the lessons learnt from the experience of the power of partnerships and social engagement through the sense of responsibility the students had gained in learn-ing how their little project meant a great deal to the community.